Two cases with postural axial tremor: Consider a genetic origin. (August 2020) - Zutt, R.; Elting, J.W.; Santens, P.; Luijckx, G.J.R.; Tijssen, M.A.J.
Abstract: We present two cases with postural axial tremor predominantly involving the head, trunk, and shoulders. In the first patient, the postural tremor occurred in multiple attacks a day lasting approximately 10 min. The second patient developed a progressive tremor of his head and arms, worsened during sitting and standing. Electrophysiological supported the postural axial tremor in both patients with a varying 3–10 Hz tremor frequency between different muscles and within the same muscles at different times. Postural axial tremor is a rare and complex movement disorder. The majority of cases are caused by acquired cerebellar pathology. However, isolated cases with underlying genetic disorders are described in literature. Here, we illustrate how to differentiate paroxysmal axial tremor from other axial hyperkinetic movement disorders and extend the genetic heterogeneity of this intriguing movement disorder phenotype. Highlights: Postural axial tremor occurs during standing/walking and decreases in a supine position. A key feature of postural axial tremor is a varying tremor frequency between muscles or within the same muscle over time. The majority of postural axial tremor is caused by acquired cerebellar pathology. With normal MRI consider genetic disorders. Postural axial tremor can have a paroxysmal nature, occurring in attacks lasting a few minutes.